A review of selected multi-criteria decision analysis techniques and applications - KS Mohamadali, Noor Azizah; Garibalidi, Jonathan (2009)
This paper presents a review of various multi-criteria decision analysis techniques. The focus of this research is to identify suitable techniques to be used to assign weights between different factors that influence user acceptance of software technology in the healthcare industry. Three widely known methodologies used for identifying, classifying and evaluating various alternatives are briefly described, namely the Analytic Hierarchy Process, Fuzzy Cognitive Maps and Fuzzy AHP, in order to identify the applicability and suitability of each in addressing our research problem.